Characterisation of a Bacterium from Selat Tebrau and Screening of Microbial Genomes for Dehalogenases: Characterisation of a bacterium from Tebrau Strait - Habeebat Adekilekun Oyewusi; Raja Nurulhafiza Raja Mohamed; Fahrul Huyop (Journal of Tropical Life Science, 2022)
Current study was to investigate the presence of dehalogenase in the isolated bacterium from Selat Tebrau that can grow on 2,2-dichloropropionic acid (2,2-DCP is an active compound in herbicide DalaponÂ®). Strain RN1, a Gram-negative and rod in shape was tentatively identified as Enterobacter cancerogenus based on basic biochemical and the 16S rRNA gene analyses. The calculated cells doubling time were 5.29 hours based on growth of the bacterium in liquid minimal media with 10, 20 and 30 mM of 2,2-DCP, respectively. However, no growth was observed at 40 mM 2,2-DCP liquid minimal medium due to increase in 2,2-DCP toxicity. It was hypothesized that, strain RN1 produced dehalogenase(s) which merits a further study of the genomic data of the same genus and species available in the database. A putative dehalogenase, designated as DehRN was located in the published data of Enterobacter cancerogenus. Pairwise of DehRN amino acids with known dehalogenase resulted in sequence identity of <20%, suggesting a new class of dehalogenase enzyme in the Enterobacter cancerogenus.Keywords: 2,2-DCP, dehalogenase, dichloropropionate, Enterobacter, haloalkanoic acid